1995
DOI: 10.1074/jbc.270.5.2047
|View full text |Cite
|
Sign up to set email alerts
|

Role for Ceramide in Cell Cycle Arrest

Abstract: The dependence of some cell types on serum factors for growth may represent a powerful, but poorly studied, model for antimitogenic pathways. In this study, we examine ceramide as a candidate intracellular mediator of serum factor dependence. In Molt-4 leukemia cells, serum withdrawal caused a significant arrest in cell cycle progression (80% of cells in G0/G1), accompanied by a modest apoptotic cell death (12%). Serum deprivation of these cells resulted in significant sphingomyelin hydrolysis (72%; correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
372
4
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 483 publications
(396 citation statements)
references
References 31 publications
16
372
4
4
Order By: Relevance
“…2), which, in our hands, was not toxic for Jurkat and primary T cells (unstimulated or preactivated). This concentration approximated levels that have previously been described to cause apoptosis in Molt-4 cells (C 6 -ceramide) and in Jurkat T cells (C 2 -ceramide), however, only after treatment for 4-6 h, respectively (32,33). In addition, C 16 -ceramide when incubated with Jurkat or primary T cells at 50 mM for 2 h did not cause detectable cell death, but a loss of stimulated membrane protrusions was observed (34).…”
Section: Discussionsupporting
confidence: 66%
“…2), which, in our hands, was not toxic for Jurkat and primary T cells (unstimulated or preactivated). This concentration approximated levels that have previously been described to cause apoptosis in Molt-4 cells (C 6 -ceramide) and in Jurkat T cells (C 2 -ceramide), however, only after treatment for 4-6 h, respectively (32,33). In addition, C 16 -ceramide when incubated with Jurkat or primary T cells at 50 mM for 2 h did not cause detectable cell death, but a loss of stimulated membrane protrusions was observed (34).…”
Section: Discussionsupporting
confidence: 66%
“…Ceramide, from the breakdown of sphingomyelin, is the major part of one of the most conserved receptor-mediated signal transduction pathways. Ceramides mediate many different cell responses such as proliferation, differentiation, growth arrest, and apoptosis (Jayadev et al, 1995;Obeid and Hannun, 1995;Pushkareva et al, 1995;Mathias et al, 1998;Claus et al, 2000;Gallardo et al, 2000). A number of different pathways are activated by ceramide through the action of ceramide-activated protein kinase (CAPK).…”
Section: Ceramide and Sphingomyelinase Apoptotic Signalingmentioning
confidence: 99%
“…Activation of this cycle through the regulation of a signal-induced sphingomyelinase (SMase) results in generation of the lipid second messenger ceramide. Ceramide then modulates a number of biological fates, including growth inhibition (1-3), differentiation (2), apoptosis (4 -6), and cell cycle arrest (7). Although recent studies have begun to catalogue inducers such as TNF␣, interleukin-1␤, nerve growth factor, and Fas that are capable of signaling through the SM cycle (see Refs.…”
mentioning
confidence: 99%
“…Two classes of lipid mediators have been implicated in TNF␣ signaling, glycerophospholipid metabolites and sphingolipid metabolites (11,12), and recent evidence suggests that these two classes of lipids may interact (13). In HL-60 cells, a linear correlation was established among TNF␣ stimulation, AA generation, and SM cycle activation: TNF␣-stimulated AA liberation preceded ceramide generation, and AA reproduced the effects of TNF␣ on the SM cycle (13). Although these studies suggested that AA and/or its metabolites may be involved in activation of SMase, the physiologic role of the PLA 2 /AA pathway in regulating SMase activity has not been determined.…”
mentioning
confidence: 99%